2009
DOI: 10.1055/s-0028-1098696
|View full text |Cite
|
Sign up to set email alerts
|

Welche Bedeutung hat die Diagnose „Pneumatosis intestinalis“ und „Portal Gas“ für den Chirurgen?

Abstract: Pneumatosis intestinalis (PI) describes the existence of gas in the wall of the gastrointestinal tract; portal gas (PG) describes gas in the portovenous system. Both are predominantly diagnosed radiologically (computed tomography as the most sensitive method) and do not represent per se self-contained syndromes, but PI and PG are possible symptoms of a variety of diseases. Possible sources of gas are bacterial gas (e. g., bowel wall invasion by aerogenic bacteria), intraluminal and extraluminal enteric gas (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It is not an independent disease but is usually accompanied by digestive tract diseases such as intestinal obstructive disease, mesenteric vascular disease, 4 gastric ulcers 5,6 gastric cancer, 7 peptic ulcers, 4 endoscopic and radiation surgery. 813 Previous reports have indicated that HPVG is often associated with severe intestinal diseases and has a mortality rate of up to 75%. 4 It is also often considered an indication for emergency abdominal surgery and has been termed the “sign of death.” As a result of the enormous progress and development in the field of medicine, Kinoshita et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is not an independent disease but is usually accompanied by digestive tract diseases such as intestinal obstructive disease, mesenteric vascular disease, 4 gastric ulcers 5,6 gastric cancer, 7 peptic ulcers, 4 endoscopic and radiation surgery. 813 Previous reports have indicated that HPVG is often associated with severe intestinal diseases and has a mortality rate of up to 75%. 4 It is also often considered an indication for emergency abdominal surgery and has been termed the “sign of death.” As a result of the enormous progress and development in the field of medicine, Kinoshita et al.…”
Section: Discussionmentioning
confidence: 99%
“…In association with portomesenteric venous gas, pneumatosis intestinalis is often a radiological sign of bowel ischemia and is associated with a high mortality rate of up to 75% [ 2 ]. However, overall, these signs do not point to specific diagnoses but are general symptoms or radiological signs, which have several medical etiologies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%